Characterization of Drosophila fruitless-gal4 transgenes reveals expression in male-specific fruitless neurons and innervation of male reproductive structures. - Billeter, J.C.; Goodwin, S.F. (Journal of Comparative Neurology, 2004)
The fruitless (fru) gene acts in the central nervous system (CNS) of Drosophila melanogaster to establish male sexual behavior. Genetic dissection of the locus has shown that one of the fru gene's promoter, P1, controls the spatial and temporal expression of male-specific FruM proteins critical to determining stereotypical male sexual behavior. By using the Gal4-expression system, we show that a 16-kb fragment of the fru P1 promoter's 5' regulatory region drives the expression of Gal4 in a subset of FruM-expressing neurons within both the pupal and adult CNS. Colocalization of FruM and a Gal4-responsive reporter shows that the fru(P1)-gal4 fusion construct generates expression in both previously characterized FruM-expressing neurons as well as within cells of both the CNS and the peripheral nervous system that have not been demonstrated as FruM-expressing. Gal4-expressing neurons are shown to innervate abdominal organs directly relevant to fru function; specifically, the muscle of Lawrence (MOL) and the male internal reproductive organs. Innervations of the latter are shown to originate from identified FruM-serotonergic neurons. Furthermore, we show that the MOL neuromuscular junction is sexually dimorphic. Finally, we describe Gal4 expression in neurites innervating male reproductive structures that are hypothesized to be targets of fru function. Isolation of the regulatory sequences controlling the expression of fru in the CNS, therefore, provides a potent tool for the manipulation of FruM-expressing neurons and for understanding the cellular basis of Drosophila reproductive behavior.